A Theoretical Modeling of Adaptive Mixed CNT Bundles for High-Speed VLSI Interconnect Design - Abu Bony Amin; Syed Muhammad Shakil; Muhammad Sana Ullah (Crystals, 2022)
The aroused quest to reduce the delay at the interconnect level is the main urge of this paper, so as to come across a configuration of carbon nanotube (CNT) bundles, namely, squarely packed bundles of mixed CNTs. The demonstrated approach in this paper makes the mixed CNT bundle adaptable to adopt for high-speed very-large-scale integration (VLSI) interconnects with technology shrinkage. To reduce the delay of the proposed configuration of the mixed CNT bundle, the behavioral change of resistance (R), inductance (L), and capacitance (C) has been observed with respect to both the width of the bundle and the diameter of the CNTs in the bundle. Consequently, the performance of the modified bundle configuration is compared with a previously developed configuration, namely, squarely packed bundles of dimorphic MWCNTs in terms of propagation delay and crosstalk delay at local-, semiglobal-, and global-level interconnects. The proposed bundle configuration is, ultimately, enacted as the better one for 32-nm and 16-nm technology nodes, and is suitable for 7-nm nodes as well.